Clinical interventions for tungiasis (sand flea disease): a systematic review. Issue 8 (August 2021) - Abrha, Solomon; Heukelbach, Jorg; Peterson, Gregory M; Christenson, Julia K; Carroll, Simon; Kosari, Sam; Bartholomeus, Andrew; Feldmeier, Hermann; Thomas, Jackson
Summary: Tungiasis (sand flea disease) is an epidermal parasitic skin disease occurring in resource-limited communities. There is no standard treatment for tungiasis, and available treatment options are scarce. To our knowledge, this is the first systematic review aimed to assess randomised controlled trials (RCTs) investigating interventions for tungiasis. We systematically searched databases including MEDLINE (EBSCOhost), CENTRAL, CINAHL, PubMed, Web of Science, SciELO, LILACS and Embase (Scopus) for RCTs in any language, from inception of the databases until June 12, 2021. RCTs exploring preventive and therapeutic interventions for tungiasis were eligible. We used the revised Cochrane Collaboration's risk of bias tool to assess the risk of bias and Jadad scale to quantify the methodological quality of the RCTs. Of the 1839 identified records, only eight RCTs involving 808 participants were included, and several methodological deficiencies were identified in most of the trials. Trial interventions included: oral drugs niridazole and ivermectin and topical interventions of ivermectin lotion, metrifonate lotion, thiabendazole lotion, thiabendazole ointment, dimeticones (NYDA), and a neem seed and coconut oils-based mixture for treatment and coconut oil-based lotion (Zanzarin) for prevention. The coconut oil-based lotion for prevention and dimeticones for treatment of tungiasis have displayed the most promise. Most of the RCTs included in this study had low methodological quality. There is a clear unmet need for high-quality RCTs examining safe and effective prevention and treatment alternatives of tungiasis in endemic settings.